PENGARUH SUMBER DAYA MANUSIA, TEKNOLOGI, DAN PENGENDALIAN INTERN AKUNTANSI TERHADAP INFORMASI PELAPORAN KEUANGAN PDAM JAMBI - Claudia, Emilia Ruth (Universitas Trilogi, 2023)
The purpose of this research aims to (1) the influence of human resource, technology, and internal control accounting on the information of financial reporting, (2) the influence of human resources towards the information of financial reporting, (3) the influence of technology towards in information of financial reporting, (4) the influence of internal control accounting towards the information of financial reporting. The sample population used in this research are the head and staff of financial, administration, and subsection in PDAM of Jambi Province. The Saturation Sampling Technique is used here. The data analysis technique used is multiple regression. The result shows that (1) the human resource, technology, and internal control accounting influences toward information of financial reporting, (2) the human resource influences toward information of financial reporting, (3) the technology not influences toward information of financial reporting, (4) the internal control accounting influences toward information of financial reporting. Keywords: Human; Information; Internal Control; Financial Reporting; Technology